GLP-1 agonists in treatment of obesity - Orłowski, Władysław; Merkisz, Konrad; Zdun, Sylwia; Walczak, Klaudia; Walczak, Patrycja; Nemeczek, Sylwia; Grzybowski, Jakub; Marciniak, Agnieszka; Jaskuła, Karolina; Grzywna, Natalia (Journal of Education, Health and Sport, 2023)
Background: Obesity is a major problem nowadays. It has correlation with metabolic and cardiovascular diseases. Due to that it is very important to diagnose and treat obesity properly. Objective: The purpose of our work is to show effectiveness of GLP1 agonist in treating obesity. Method: A literature review was conducted in PubMed database using the key words: „Semaglutide obesity” „Tirzepatide obesity” „Liraglutide obesity” „obesity”. Results: Using particular drug in addition to lifestyle modification appears to be more effective than using placebo with lifestyle modification. Conclusions: Trials showed effectiveness of GLP1 analogs in treatment of obesity. These drugs might be a future of managing with obesity, but we do not know yet how long lasting is the effect of these drugs. The upcoming years will bring us more trials, but in this moment we can say that they have a lot of potential.